2017
DOI: 10.4172/2329-6607.1000e133
|View full text |Cite
|
Sign up to set email alerts
|

Trials Evaluating Ticagrelor in Cardiovascular Disease: Will It Reign Supreme in the Anti-Platelet World?

Abstract: EditorialTicagrelor and prasugrel are newer and stronger platelet P2Y12 receptor antagonists than their predecessor clopidogrel. Clopidogrel is a pro-drug requiring a 2-step hepatic activation processes. Speed of activation varies according to the cytochrome P-450 2C19 allele [1,2]. Ticagrelor is a direct non-thienopyridine P2Y12 antagonist producing equal or stronger inhibition of the P2Y12 receptor even when compared to the newer thienopyridine prasugrel [3]. The PLATO TrialIn the PLATO trial of 18624 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…PRECISE-DAPT score does not assess the underlying ischemic risks, so utility may be limited. As previously discussed in the journal [3], there was another recent patient-level meta-analysis [7] of 11473 patients with coronary stenting from 6 randomized trials (58.5% with stable disease) which showed that the initial presentation altered outcome after different durations of DAPT: Patients with ≥6 month DAPT tended to have higher 1-year event rates of myocardial infarction or stent thrombosis than patients with 1-year DAPT if they had unstable disease (HR 1.48; 95% CI, 0.98-2.22) but not if they had stable disease (HR 0.93; 95% CI, 0.65-1.35).…”
Section: Precise-dapt Versus Daptmentioning
confidence: 70%
See 4 more Smart Citations
“…PRECISE-DAPT score does not assess the underlying ischemic risks, so utility may be limited. As previously discussed in the journal [3], there was another recent patient-level meta-analysis [7] of 11473 patients with coronary stenting from 6 randomized trials (58.5% with stable disease) which showed that the initial presentation altered outcome after different durations of DAPT: Patients with ≥6 month DAPT tended to have higher 1-year event rates of myocardial infarction or stent thrombosis than patients with 1-year DAPT if they had unstable disease (HR 1.48; 95% CI, 0.98-2.22) but not if they had stable disease (HR 0.93; 95% CI, 0.65-1.35).…”
Section: Precise-dapt Versus Daptmentioning
confidence: 70%
“…The benefit-torisk assessment for longer versus shorter duration of DAPT depends on the coronary ischemic risks, the nature of antiplatelet medications and the general bleeding risks. Previous editorials in the journal have addressed in part the former 2 issues [1][2][3] and the current editorial will focus on the last and integrate them in clinical application.…”
Section: Editorialmentioning
confidence: 99%
See 3 more Smart Citations